Redesign UI/UX dengan Metode SUS dan UCD pada Website Akademik UHAMKA - Kurniyawan, Ahmad Barkah; Irwansyah, Irwansyah (METIK JURNAL (AKREDITASI SINTA 3), 2025)
The advancement of information technology has encouraged higher education institutions to provide more efficient and accessible digital academic services. Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA) utilizes a web-based academic information system to support student activities such as course registration (KRS), grade management, payments, and schedule information. However, the existing system still faces challenges related to user interface and user experience, including monotonous design, unintuitive navigation, and inconsistent interface elements. This study aims to redesign the user interface (UI) and user experience (UX) of UHAMKA’s academic system using the User-Centered Design (UCD) approach and to evaluate the results through the System Usability Scale (SUS) method. The prototype was developed using the Figma platform. The research methodology involved observation, questionnaire distribution, and interviews with 35 active students. The initial evaluation yielded a SUS score of 40.07, which falls into the “Poor” and “Not Acceptable” categories. After redesigning seven main pages and one additional page, the prototype was re-evaluated and achieved a SUS score of 80.71, categorized as “Excellent” and “Acceptable.” Post-redesign interviews also indicated improvements in user comfort, information clarity, and ease of navigation. The primary contribution of this study lies in demonstrating a significant improvement in system usability through a systematic application of the UCD approach, and the resulting design may serve as a reference for developing more user-centered digital academic systems.